THE ROLE OF LOCAL GOVERNANCE IN DISASTER PREPAREDNESS AND RESPONSE SYSTEMS AND ENHANCING COMMUNITY RESILIENCE (Lex localis - Journal of Local Self-Government, 2025)
This research explores the critical role of local governance in disaster preparedness and response systems, focusing on enhancing community resilience. It examines how local governments contribute to the effectiveness of disaster management by utilizing a combination of strategies, including community engagement, resource allocation, and coordination with external agencies. The study employs a mixed-method approach, combining case studies, expert interviews, and statistical analysis. The findings demonstrate that decentralized governance, characterized by strong local leadership and community involvement, significantly enhances disaster resilience. The study highlights key factors, including communication, planning, and resource management, which contribute to effective disaster response.